Acute Effects of Elastic Bands on Kinetic Characteristics During the Deadlift at Moderate and Heavy Loads. Issue 12 (December 2015) - Galpin, Andrew J.; Malyszek, Kylie K.; Davis, Kyle A.; Record, Shaina M.; Brown, Lee E.; Coburn, Jared W.; Harmon, RoQue A.; Steele, Jeff M.; Manolovitz, Adam D.
Abstract : Abstract: Galpin, AJ, Malyszek, KK, Davis, KA, Record, SM, Brown, LE, Coburn, JW, Harmon, RA, Steele, JM, and Manolovitz, AD. Acute effects of elastic bands on kinetic characteristics during the deadlift at moderate and heavy loads. J Strength Cond Res 29(12): 3271–3278, 2015—Loading a barbell with variable resistance positively alters kinetic characteristics during the back squat and bench press but has never been studied during the deadlift. The purpose of this project was to examine the acute effects of combining elastic bands and free weights during the deadlift at moderate and heavy loads. Twelve trained men (age: 24.08 ± 2.35 years, height: 175.94 ± 5.38 cm, mass: 85.58 ± 12.49 kg, deadlift 1 repetition maximum (RM): 188.64 ± 16.13 kg) completed 2 variable resistance (B1 and B2) and 1 traditional free-weight (NB) condition at both 60 and 85% 1RM on a force plate. B1 had 15% resistance from bands, with the remaining 85% from free weights. B2 had 35% bands and 65% free weights. NB used free weights only. Average resistance was equated for all conditions. Power and velocity generally increased, whereas force decreased with the addition of bands. The amount of band tension (B1 or B2) had little impact on power when lifting at 60% 1RM. However, greater resistance from bands resulted in greater peak and relative power when lifting at 85% 1RM. Adding elastic bands decreased time to peak force (PF), time between PF and peak power (PP), and time between PF and peak velocity (PV) when compared with NB at 60% 1RM (NB > B1 > B2). These differences only reached significance for NB > B2 when lifting at 85% 1RM. These same differences existed for time between PP and PV. Thus, the amount of tension from bands has less impact on interpeak variables at heavier absolute loads. Practitioners should consider using heavy bands when prescribing the deadlift for speed or power, but not maximal force.